Strategy for Implementing @Asahpolapikir TikTok Account Content as a Learning Media for Students - Kurniawan, Jasen; Aripradono, Heru Wijayanto; Ardiansyah, Muhammad (Jurnal Info Sains : Informatika dan Sains, 2024)
In this digital era social media has become an inseparable part. This can lead to various issues such as stress triggered by negative behaviors like body shaming and cyberbullying on social media, but social media TikTok can be utilized as an educational platform, particularly for enhancing media literacy and analytical skills. Through TikTok, students can explore various topics such as education, health, beauty and culinary arts. Additionally, TikTok serves as a platform for religious outreach, where professionals and the general public share knowledge through short videos. The focus of this research is the TikTok account @asahpolapikir, owned by Tjokro Wimantara who has built a strong personal brand through consistent content on education, business, entrepreneurship, and marketing strategies. With 2.1 million followers, @asahpolapikir won the TikTok Awards in the Best of Learning and Education category for its impactful content. This study adopts a qualitative approach using descriptive methods. The content posted by @asahpolapikir that garnered the most views and likes focuses on the challenges faced by undergraduate students in finding jobs and the importance of work experience. Additionally, the content about renting shop spaces for business purposes also received a high response, with 1.3k comments, due to its relevance to students interested in entrepreneurship. It can be concluded that the content strategy of the TikTok account @asahpolapikir prioritizes content with an educational approach, awareness of reality, and practical solutions, which are effective in capturing attention and increasing interaction on TikTok.